HUBUNGAN MORAL DISENGAGEMENT DENGAN TINGKAT CYBERBULLYING PADA DEWASA MUDA - Pipih Murtapiah; Naomi Soetikno (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The phenomenon of cyberbullying in Indonesia is not new. Cyberbullying has become a serious concern, especially among young adults who are active users of social media. Various forms of cyberbullying exist, such as negative comments, posts that harm others, and other forms of repeated bullying on social media. The conditions of young adulthood open up opportunities for moral justification or moral disengagement in negative behavior. The impact of moral disengagement is not limited to moral justification, but can be broader, leading to cyberbullying behavior that is considered normal. This study aims to determine the relationship between moral disengagement and the level of cyberbullying among young adults. This study uses a quantitative method with a correlational design and purposive sampling technique. There were 269 participants aged 18-25 years old who had engaged in cyberbullying and were active social media users. Data were collected through an online questionnaire using Google Forms via a digital platform. The research instruments used were the Cyberbullying Offending Scale (COS) and The Mechanism of Moral Disengagement Scale (MMDS). The results of the Spearman Rho correlation analysis showed a positive relationship between moral disengagement and the level of cyberbullying (r = 0.739, p < 0.001), which means that the higher the moral disengagement, the higher the level of cyberbullying. This study is useful for advancing the field of psychology, particularly regarding moral disengagement and cyberbullying, and is also beneficial for social media platform users in avoiding cyberbullying.